The Free Nutritious Meal Program and Early Childhood Learning Readiness: A Case Study from Indonesia - Ferlinda Eka Agholin Rahayu; Vinandiya Muhtarisul Lisaniyah; Syifa Almuk Minun; Khaled Ahmed Aqeel Alzoubi; Konstantinos T. Kotsis; Fani Endang Setia Ningsih (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Nutritional problems in early childhood remain a major challenge in Indonesia, particularly among low-income families who struggle to meet children’s nutritional needs. According to the 2023 Indonesian Health Survey, the national stunting prevalence reached 21.5%, indicating that one in five children experiences growth impairment due to chronic malnutrition. In response to this issue, the Indonesian government launched the Free Nutritious Meal (FNM) Program in January 2025 as a strategic initiative to reduce stunting and improve human resource quality from an early age. Aims and scope of paper: This study aims to analyze the implementation of the FNM program at RA Muta’alimin Labang, focusing on the types of services provided, the implementation process, challenges encountered, and the program’s initial benefits for children’s nutritional status and learning motivation. Methods: The study employed a qualitative approach using a case study design. Research participants included the school principal, classroom teachers, and parents, selected through purposive sampling. Data were collected over four months through participatory observation, in-depth interviews, and document analysis. Data analysis followed the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. Results: The findings indicate that the FNM program was implemented consistently from Monday to Friday at 09:00 a.m. and had a positive impact on children’s attendance and learning enthusiasm. Children who received adequate nutritional intake demonstrated improved concentration, higher levels of classroom participation, and increased learning engagement. Contribution: This study provides empirical evidence that the FNM program enhances children’s physical health and cognitive readiness for learning. Beyond its empirical findings, the study makes a conceptual contribution to the international early childhood education literature by reframing nutrition-based interventions as a foundational component of the learning readiness framework. It demonstrates how nutritional status operates as a mediating mechanism linking physical health, cognitive preparedness, and early learning outcomes, offering a theoretically transferable model that is applicable across diverse early childhood education contexts, particularly in settings where nutritional vulnerability shapes educational trajectories.